On the Evolution of Music Notation in Network Music Environments. - Hajdu, Georg; Didkovsky, Nick (Contemporary Music Review, 2009)
Over the past two decades the computer music community has observed the gradual development of network music performance environments that encompass a large spectrum of features ranging from audio streaming to the rendering of scores in various styles. This article gives a short historical overview of these developments and elaborates on two environments created by the authors: Java Music Specification Language (JMSL) by Nick Didkovsky, and Quintet.net by Georg Hajdu. MaxScore, a recent adaptation of JMSL's standard music notation package to the graphical programming environment MaxMSP, has provided the tools for sophisticated real-time music notation in network music performance which, accompanied by conducting tools (instant messaging, annotations, cursors, metronomes, light controllers), facilitate rehearsals and performances of music in computer networks.